IMPLEMENTASI CORPORATE SOCIAL RESPOSIBILITY CV. KARYA PERDANA DI DESA SUMBERMULYO DALAM PERSPEKTIF ETIKA BISNIS ISLAM - Fiqih Zulianih; Ashlihah -; Amin Awal Amarudin (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2020)
To ensure that the strategy is successful, organizational policies will be needed to prepare the facilities needed to solve the problems that arise during implementation. CV policy. Karya Perdana in a company that includes corporate social responsibility which is the basis for the company manager CV. The Initial Work so that CSR is in line with the company's vision and mission and objectives in accordance with the CSR policies in force in the community. This study is an evaluative study of the implementation of Corporate Social Responsibility in the perspective of Islamic business ethics with a qualitative approach. data analysis using interviews, documentation, and observation. The results of this study indicate that the implementation of Corporate Social Responsibility conducted on the CV. Perdana's work in Sumbermulyo village is in accordance with Islamic business ethics. This can be seen from CSR using Islamic business ethics principles such as: unity (divinity), Eqieulibrium (balance), free will (free will), responsibility (responsibility) and ihsan (expediency). The concept with the concept of Islam according to Al-Ghozali is done to eliminate all difficulties and inconveniences, as well as improve the quality of life morally and materially so that it can prosper the community.